Fatigue following radiotherapy of low-risk early breast cancer - a randomized controlled trial of intraoperative electron radiotherapy versus standard hypofractionated whole-breast radiotherapy: the COSMOPOLITAN trial (NCT03838419) - Forster, Tobias; Jäkel, Cornelia; Akbaba, Sati; Krug, David; Krempien, Robert; Uhl, Matthias; Häfner, Matthias; König, Laila; Körber, Stefan A.; Harrabi, Semi B.; Bernhardt, Denise; Behnisch, Rouven; et al. (Radiation oncology, 2020)
Fatigue is one of the most common and distressing side-effects of breast cancer radiotherapy. According to current guidelines, accelerated partial breast irradiation (APBI) may be considered as an alternative treatment option for women with early-stage low-risk breast cancer. One method for APBI is single-dose intraoperative radiotherapy (IORT) applied directly to the tumor bed during breast conserving surgery (BCS). The COSMOPOLITAN trial therefore aims to analyze the intensity of fatigue following single-shot IORT with electrons (IOERT) compared to conventional hypofractionated whole breast irradiation (WBI) in low risk early breast cancer patients.